2019
DOI: 10.3897/neotropical.14.e49079
|View full text |Cite
|
Sign up to set email alerts
|

Características reprodutivas de peixes invasores no rio Paranapanema, bacia do alto rio Paraná, sul do Brasil

Abstract: Estudos sobre biologia reprodutiva podem fornecer explicações sobre o sucesso na colonização de novas áreas, dado que características biológicas associadas às espécies invasoras podem conferir vantagem na invasão. Objetivamos avaliar variações de características reprodutivas de peixes invasores em lagoas e rios livres de barragens. Foram estudadas populações de Serrasalmus marginatus, Loricariichthys platymetopon, Ossancora eigenmanni, Auchenipterus osteomystax e Trachelyopterus galeatus em habitat lêntico (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
7
0
4
Order By: Relevance
“…Several theories about biological invasions have shown that the success of invasive species depends on biotic (Elton 1958) and abiotic factors (Davis et al 2000), or an interaction between the two (Lockwood et al 2005). According to Garcia et al (2019), there is not a set of resources capable of predicting which species of fish can be successful in the invasion; however, both the biological characteristics and the degree of impact of the invaded area can facilitate the establishment and dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Several theories about biological invasions have shown that the success of invasive species depends on biotic (Elton 1958) and abiotic factors (Davis et al 2000), or an interaction between the two (Lockwood et al 2005). According to Garcia et al (2019), there is not a set of resources capable of predicting which species of fish can be successful in the invasion; however, both the biological characteristics and the degree of impact of the invaded area can facilitate the establishment and dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Species with generalist reproductive and trophic niche strategies are more likely to have invasion success (Agostinho et al 2007(Agostinho et al , 2016Garcia et al 2018aGarcia et al , 2018bGarcia et al , 2019. Galvão et al (2016) observed that P. kennedyi might be sexually mature throughout the year, with both females and males with three stages of gonadal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of non-native fishes present in the Lower Paranapanema river basin (Garcia et al 2018a;Jarduli et al 2020) shows that this stretch of the river presents several optimal environmental conditions and resources for fish species in the system (Blackburn et al 2011;Garcia et al 2018bGarcia et al , 2019. Biological invasion is one of the main drivers of biodiversity loss and ecosystem damage.…”
Section: Introductionmentioning
confidence: 99%
“…e Xiphophorus spp. mantêm embriões internamente no corpo da fêmea), aumentando a chance de sobrevivência dos filhotes (Garcia et al 2019a). Por outro lado, as espécies que apresentam alta fecundidade e liberam seus gametas diretamente na água, como as carpas e Carassius auratus (Cypriniformes, Cyprinidae), levam vantagem por produzir uma prole numerosa, desde que o ambiente seja propício ao seu desenvolvimento (Moyle & García-Berthou 2011, Magalhães & Jacobi 2013.…”
Section: Por Que Algumas Introduções Falham E Outras Têm Sucesso?unclassified